Advanced urban transport - Black, Ian; Richard, Gille; University of Warwick (Farnborough, Hants. : Saxon House ; Lexington, Mass. : Lexington Books, 1975)
This book presents issues on design, assessment or operation of such system
Includes bibliographical references and index.
mf24/01/2019
Loans
Keywords: Local transit